The Green GDP Implementation in Country-Based Environmental Management System: A Review - Filson Maratur Sidjabat; Asyifa Apsari (Jurnal Serambi Engineering, 2020)
The economy, environment, and social pillars of sustainability demand the environmental management system (EMS) to improve the cycle system continuously. The result of the evaluation and review stages needs to account for the measurement method that potentially enhances the policy implication. Thus, the green GDP found to be practically suited with current country-based EMS, where it shows by China’s green GDP and GDP gap reached 5% in 2016. The objective of this paper is to acknowledge the implementation of green GDP in the country-based environmental management system. This paper is based on a literature review process, which covered around eight references. The result and discussion lead to the implementation of green growth indicator in national and regional green economy strategy of Indonesia, China, and Finland. The challenges of unstandardized indicators and calculation formula prospected to be tackled by reflecting the current indicator with potential global adjusted formula and valuation through international policy enforcement and integrated communication. The conclusion describes that green GDP is potentially integrated with EMS to ensure the improved cycle of sustainability.